Enhancement of in vitro protein digestibility of palm kernel cake by extrusion - Roslan, Muhamad Akhmal Hakim (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
The palm kernel (PKC), a by-product from the oil palm industry, was physically treated by extrusion to enhance its nutritive value. A twin-screw extruder was used and the conditions tested were based on the Box-Behnken design. The four controlled variables were: extrusion temperature (80-180ºC), screw speed (100-300rpm), hopper speed (5-15Hz) and PKC moisture content (30-60%). The in vitro protein digestibility (IVPD) of the treated PKC was measured by using a multi-enzyme system consisting of trypsin, α-chymotrypsin and peptidase. The results showed that the values of IVPD under different extrusion conditions were from 69.1% to 92.3%. The extrusion process significantly improved IVPD of PKC. According to the regression coefficients significance of the second-order model, the optimum extrusion parameters for the maximum digestibility was obtained when the extrusion temperature was102ºC; screw speed, 111rpm; PKC moisture content, 36%; and hopper speed, 7.6Hz. Under these conditions, the IVPD of PKC increased from 80.2±0.07%to 93.2±0.06%.